Bahasa Inggris - Nurul Muhliza; Abd. Rahim; Citra Ayni Kamaruddin; Sri Astuty; Irwandi Irwandi (Jurnal Wacana Ekonomi, 2025)
This quantitative research aims to analyze the influence of Government Expenditure in the Education Sector, Health Sector, and Minimum Wage (UM) on Poverty in five districts with the highest poverty rates in South Sulawesi Province (Pangkep, Jeneponto, Luwu, North Luwu, and Enrekang), utilizing annual panel data spanning the 2015 to 2024 period. Through a series of model tests, the Fixed Effect Model (FEM) estimated using the Least Square Dummy Variable (LSDV) approach was determined as the best method. The estimation results show that simultaneously, the three independent variables significantly affect poverty, with the model's explanatory power (Adjusted R-Squared) reaching 77.4%. However, the partial results (t-test) reveal that only the Minimum Wage variable has a negative and significant influence in reducing poverty (Prob. 0.0079). Conversely, although Government Expenditure in the Education Sector has a positive coefficient (Prob. 0.9123) and the Health Sector has a negative coefficient (Prob. 0.4973), both are not statistically significant in influencing poverty reduction. This study concludes that policy intervention through setting adequate wages is the most effective tool in poverty alleviation efforts in the research area, while the effectiveness of public spending in the education and health sectors requires further review to ensure its long-term impact.